Evaluation of local and regional air quality forecasts for London. (11th April 2019) - Stidworthy, Amy; Jackson, Mark; Johnson, Kate; Carruthers, David; Stocker, Jenny
This paper presents key results from the evaluation of a local-scale air quality forecasting system, air TEXT, alongside the CAMS regional-scale air quality forecast. The CAMS forecast, which is used to account for the long-range transport of pollutants within air TEXT, is adjusted to account for the apparent bias in concentrations predicted within the south-east of England. Forecasts of the UK Daily Air Quality Index metrics for NO2, O3, PM10 and PM2.5 in London have been assessed using the Model Evaluation Toolkit and the DELTA Tool for a five month period during 2017. For NO2, where air pollutant concentrations are primarily a result of local emissions, the local forecast performs significantly better than the regional forecast as the steep roadside concentration gradients are resolved by ADMS-Urban, the dispersion model used within air TEXT. Although regional O3 and particulate forecasts dominate the local forecasts, air TEXT also performs better than CAMS for these pollutants by accounting for emissions, dispersion and chemistry at high spatial resolution.